Quasirandomness in hypergraphs - Aigner-Horev, E; Conlon, D; Han, H; Person, Y; Schacht, M (Electronic Journal of Combinatorics, 2018)
An n-vertex graph G of edge density p is considered to be quasirandom if it shares several important properties with the random graph Gpn, pq. A well-known theorem of Chung, Graham and Wilson states that many such ‘typical’ properties are asymptotically equivalent and, thus, a graph G possessing one such property automatically satisfies the others. In recent years, work in this area has focused on uncovering more quasirandom graph properties and on extending the known results to other discrete structures. In the context of hypergraphs, however, one may consider several different notions of quasirandomness. A complete description of these notions has been provided recently by Towsner, who proved several central equivalences using an analytic framework. We give short and purely combinatorial proofs of the main equivalences in Towsner’s result.